Managing COVID-19 Challenges: Strategies to Keep students Engaged in Online Learning - A Case study of Kepler - Vedaste Nsengiyumva; Jean Bosco Sibomana; Christian Shema Nsenga (International Journal of Humanities and Education Development (IJHED), 2022)
This article is about strategies devised by Kepler in reaction to challenges brought in by the covid-19 outbreak since its occurrence in 2019. Kepler instructors have devised a number of tools and strategies in order to cope up with the challenges and keep students engaged as the institution, like many others, had shifted from blended to online (or remote) learning. The study analyzed the effectiveness of the tools and strategies used to keep students engaged in remote learning. We collected data from 169 out of 174 students who were in the program, and 18 out of 25 instructors who were teaching during the pandemic time. Online surveys were sent to both students and teachers to collect quantitative data. The students and teachers involved in this study gave their views about the usefulness of the tools and strategies used, and the report shows that the tools contributed to students' engagement and helped them to curb the challenges they had faced. The study recommends the use of recording online tools such as vocaroo.com, speakpipe.com; self-paced quizzes, videos, podcasts, discussion boards, shared google docs, and strategies like peer reviews, feedback, icebreakers, warm up prompts, higher order thinking questions, and class final reflections, as the respondents reported that they helped them stay engaged, which would not have been possible if the instructors used the traditional lecture method and online group assignments only during the virtual teaching and learning. The findings in this paper will contribute to the improvement of online teaching and learning strategies